2011
DOI: 10.3109/10253890.2010.545459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of academic psychological stress in post-graduate students: The modulatory role of cortisol on superoxide release by neutrophils

Abstract: Experimental and clinical evidence shows that neutrophils play an important role in the mechanism of tissue injury in immune complex diseases through the generation of reactive oxygen species. In this study, we examined the influence of academic psychological stress in post-graduate students on the capacity of their blood neutrophils to release superoxide when stimulated by immune complexes bound to nonphagocytosable surfaces and investigated the modulatory effect of cortisol on this immune function. The tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
1
14
0
1
Order By: Relevance
“…The present finding on the effects of examination stress on serum cortisol levels differ from earlier studies in many aspects. Firstly, whereas other studies reported hypercortisolism in association with the examination stress (Bardi et al 2011;Ignacchiti et al 2011;Kamezaki et al 2012;Katsuura et al 2012), the present study also investigated changes in cortisol levels due to subjective differences in the perception of academic examination stress. We assessed subjective differences in the perception of examination stress with a self-report measure and found that most students were in mild or moderate stress and the greater was the perception of stress more were the increases in HPA axis activation (Figs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present finding on the effects of examination stress on serum cortisol levels differ from earlier studies in many aspects. Firstly, whereas other studies reported hypercortisolism in association with the examination stress (Bardi et al 2011;Ignacchiti et al 2011;Kamezaki et al 2012;Katsuura et al 2012), the present study also investigated changes in cortisol levels due to subjective differences in the perception of academic examination stress. We assessed subjective differences in the perception of examination stress with a self-report measure and found that most students were in mild or moderate stress and the greater was the perception of stress more were the increases in HPA axis activation (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, there can be enormous variability among individuals in physiological reactions and basal levels of cortisol may also differ among individuals despite lack of differences in perceived stress. Compared with previous studies measuring circulating levels of cortisol on the day of examination (Bardi et al 2011;Ignacchiti et al 2011), we also monitored cortisol response in the beginning of academic session to compare it with the response on the day of examination (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…In phagocytes, an inhibitory effect of the HPA axis on the NADPHderived oxidative stress has been reported. Thus, hydrocortisone has been shown to inhibit the generation of NOXderived superoxide and to suppress the expression of the p47 phox subunit (78,117,169). Similarly, in human aortic smooth muscle cells, an inhibitory effect of glucocorticoids on superoxide production and on the mRNA expression of the p22 phox subunit has been described in (111).…”
mentioning
confidence: 94%
“…Interestingly, the level of FcγR and complement receptor expression, as well as the functional responsiveness of neutrophils from patients with rheumatoid arthritis, systemic lupus erythematosus, and Graves' disease obtained by the gelatin method can be distinguished from those of healthy individuals' neutrophils in the resting state (Marzocchi-Machado et al, 2002;Russo-Carbolante et al, 2005;Paoliello-Paschoalato et al, 2011). Neutrophils from students under psychological stress, isolated by the gelatin method, displayed reduced level of superoxide anion production and mRNA expression for the p47 phox subunit of the NADPH oxidase complex, in comparison to control individuals (Ignacchiti et al, 2011). Stie and Jesaitis (2004) have reported that the gelatin method primes neutrophils and induces the release of secretory vesicles; however, these authors processed a large blood volume (500 mL) and used ice-cold erythrocyte lysing solutions, which probably affected the neutrophil activation state.…”
Section: Discussionmentioning
confidence: 96%